A comprehensive approach to drought and desertification in Nigeria: A brief evaluation of government policies - Medugu, Idris Nasiru; Majid, Mohammed Rafee; Choji, I. D. (Emerald Group Publishing Limited, 2008)

(untitled)
Purpose – The main purpose of this paper is to evaluate current government policies in combating desertification and mitigating the effects of drought. This paper discusses the menace of desertification, the extent and the impact of drought in Nigeria. Design/methodology/approach – The research reported in this paper was undertaken through review of existing literature, personal observations and interview with some of the residents in the affected areas as well as government officials in charge of programs in combating desertification. Findings – The paper observes that the failure of current government policies include among others the top-down approach, inconsistencies of government policies, neglect of indigenous knowledge, use of inappropriate technology, sectoral approach, inadequate funding, and inadequate awareness. Having identified the causes of the problem, this paper proposes that the national policy for drought and desertification should ensure sustainable development based on proper management of human-environment interactions in the affected areas. Practical implications – The evaluation method performed in this paper allows us to analyze the factors responsible for the failure of government policies in combating desertification in Nigeria. This paper suggests that a number of complementary policies, strategies and management approaches be put in place and such must take cognizance of the existing institutional settings and professional groupings as well as the complex historical, social, cultural, and legal considerations. Originality/value – The paper provides a rational, holistic, practicable and comprehensive approach for finding solutions to the problems of drought and desertification in Nigeria.